NUTRITIONAL EDUCATION EFFECTS ON KNOWLEDGE CHANGE, ATTITUDE AND CHANGES IN CONSUMPTION PATTERNS AND OBESITY SEDENTARY ADOLESCENT ACTIVITIES - Ikbal Mahdali (Jambura Journal of Sports Coaching, 2019)
This study aims to determine the effect of nutritional education on changes in knowledge, attitudes and behavior changes in obese adolescents. This study was an experimental study with a pre-post test randomized controlled group design. The study population was obese students aged 12-15 years in Gorontalo 1 Public Middle School. The sample was taken by purposive sampling. The results of the study were in the treatment group before being given nutrition education there were several foods that exceeded the standard score. After being educated there was a decrease in food that exceeded the standard score. There was a change of knowledge in respondents after nutrition education in the good category increased by 18% (p 0.05). For the attitude, variable changes occur after nutrition education, namely the treatment of respondents' positive attitudes increased by 30% (p 0.05). For breakfast variables, there was a change in breakfast for respondents after nutrition education. Can be seen in the breakfast treatment group the good category of respondents increased by 48% (p 0.05). For the variable sedentary activity, changes occur after nutritional education. Can be seen in the treatment group sedentary activity in the high category of respondents decreased by 32% (p 0.05). Conclusion: There was an increase in knowledge, positive attitude, breakfast habits due to nutrition education of overweight / obese adolescents.